AN ANALYSIS OF SYMBOLS FROM GUA CEREMONY OF OLAIA SOCIETY - Sergius Alpini; Sujito Sujito; Maria G Sri Ningsih (Fakultas Bahasa dan Sastra Universitas Kanjuruhan Malang, 2016)
Gua Ceremony is part of Olaia tradition and an event which is interesting to analyze because there are many kinds of symbols used in it. Gua ceremony is not separated from language. By using language, we can express our thought, idea, emotion, and feeling, because language is an important aspect of human life and social communication among the members of society. It is interesting to study Gua ceremony linguistically, especially in semantic. Therefore, the researcher is interested in studying this problem by formulating five researcher problems such as: how does the process of implementation of Gua ceremony on Olaia village, sub-district Aesesa, District Nagekeo,what are the symbols and symbols meaning on Olaia village, sub-district Aesesa, District Nagekeo. What are functions of Gua ceremony on Olaia village, sub-district Aesesa, District Nagekeo, and What are values appeared from Gua ceremony on Olaia village, sub-district Aesesa, District Nagekeo? This study has two significances of the study, theoretically and practically. Theoretically, the result of this study will give the description about the symbols used in Gua ceremony. Practically, the researcher hopes this research is useful to enrich the description of Gua ceremony and as additional knowledge for people or student both from Nagekeo or others. The research of this thesis is qualitative research. It is intended to describe about the symbols, and also their meaning used in Gua ceremony. Besides the researcher himself as the key instruments, the instruments used in this study are documentation, observation, and interview. From the result of this study, it was obvious that Gua ceremony used some symbols. And every symbol has its own meaning.